Flipped classroom teaching methods in medical education - Tremonti, Christopher (2018)
BACKGROUND: Recent rapid increases in technology development have become increasingly prevalent in education. As a result of online education resources, classroom teaching dynamics have begun to shift away from traditional lecture. In particular, flipping the classroom has become popular in higher education. Flipping the classroom consolidates standard lectures into at-home self-study modules, and utilizes class time for engaging students in critical thinking exercises. Some research suggests that this style of teaching has led to increased student satisfaction and higher exam scores. OBJECTIVES: The objective of this study is to compare flipped classroom modules to traditional lecture in PA and medical student didactic education. METHODS: This study is a crossover interventional study that includes first year PA students and second year medical students from Boston University. Students will be randomly assigned to either a control group or experimental group. Both groups will take three tests throughout the study: a pre-test prior to intervention, a test following the first week prior to crossover, and a final exam after crossover completion. Each exam will consist of 30 multiple choice questions and a Likert scale questionnaire assessing student satisfaction. The control group will be exposed to traditional lecture while the experimental group will be exposed to a flipped classroom module. Content will be identical between groups, and following module completion, the groups will crossover for exposure to opposing treatment. RESULTS: Each cohort’s exam scores will be evaluated based on mean score and standard deviation at all three time points. Additionally, Likert scale responses will be evaluated at all three time points. Values will be assessed to determine if a relationship between lecture style, exam scores, and student satisfaction exist. DISCUSSION: Results from this study will help to determine the significance of flipped classroom learning in medical education.